Using nonhuman culture in conservation requires careful and concerted action. Issue 2 (6th January 2022) - Carvalho, Susana; Wessling, Erin G.; Abwe, Ekwoge E.; Almeida‐Warren, Katarina; Arandjelovic, Mimi; Boesch, Christophe; Danquah, Emmanuel; Diallo, Mamadou Saliou; Hobaiter, Catherine; Hockings, Kimberley; Humle, Tatyana; Ikemeh, Rachel Ashegbofe; et al.
Abstract: Discussions of how animal culture can aid the conservation crisis are burgeoning. As scientists and conservationists working to protect endangered species, we call for reflection on how the culture concept may be applied in practice. Here, we discuss both the potential benefits and potential shortcomings of applying the animal culture concept, and propose a set of achievable milestones that will help guide and ensure its effective integration existing conservation frameworks, such as Adaptive Management cycles or Open Standards.